Silicon carbide radiation detectors for medical applications - Nurul Syazwina, Mohamed (2017)
There is increasing interest in the development of radiation hard detector materials with the capability to discriminate within wide dose range and high radiation tolerance that are sensitive, and show a linear response. In this study, fabricated 4H-SiC Schottky diodes were exposed to dose rates ranging from 0.02 to 0.185 mGy/min to analyse the linearity and sensitivity at room temperature. High linearity response presented from the graph of current signal plotted versus dose rate which show enhancement of 104 in comparison to previous studies. The sensitivity measured at different bias voltages by exposing to 0.185 mGy/min dose rate show good reproducibility and stability of the current signal with time. Collected charge presented for all diodes exhibit linear behaviour of photon induced collected charge with the sensitivity between 1.40 to 8.38 x 105 nC/Gy for the 0.20 to 1 mGy absorbed dose range. Thus, these devices are ideally suited for the realisation of radiation detectors at moderate dose range.